Tekun Resmi Staff Management System - binti Ramzei, Nuramirah Afifah; binti Mohamed, Rozlini (Applied Information Technology And Computer Science, 2024)
The company Tekun Resmi Sdn Bhd is now operating a cleaning service business and due to a lack of technological expertise, they had difficulty managing staff information by physically recording staff data and keeping it in files or on documents. The objectives of this project are to design, to create management system by using web-based approach and to test the web-based staff management system. This project’s activities are guided by the waterfall development method and the system is built with Visual Studio Code and phpMyAdmin as database. This system consists of four functional modules, including staff information, attendance, leave, and payroll, and there are two different types of users: administrators and employees. The administrator can view staff information such as leave, attendance, salary, and personal details, other than that the administrator can also handle salary and leave applications submitted by employees. The system also allows staff to key-in their attendance, apply for leave, update information and view salary and personal information. In generally, the system works as a platform to strengthen interactions between employers and employees and enhances the effectiveness of the company’s staff’s management system. It will be easier for the company to manage all the information efficiently and effectively.